Enhanced Efficacy of Human Brain-Derived Neural Stem Cells by Transplantation of Cell Aggregates in a Rat Model of Parkinson's Disease - Shin, Eun Sil; Hwang, Onyou; Hwang, Yu-Shik; Suh, Jun-Kyo Francis; Chun, Young Il; Jeon, Sang Ryong (KOREAN NEUROSURGICAL SOC, 2014)
Objective : Neural tissue transplantation has been a promising strategy for the treatment of Parkinson's disease (PD). However, transplantation has the disadvantages of low-cell survival and/or development of dyskinesia. Transplantation of cell aggregates has the potential to overcome these problems, because the cells can extend their axons into the host brain and establish synaptic connections with host neurons. In this present study, aggregates of human brain-derived neural stem cells (HB-NSC) were transplanted into a PD animal model and compared to previous report on transplantation of single-cell suspensions. Methods : Rats received an injection of 6-OHDA into the right medial forebrain bundle to generate the PD model and followed by injections of PBS only, or HB-NSC aggregates in PBS into the ipsilateral striatum. Behavioral tests, multitracer (2-deoxy-2-[F-18]-fluoro-D-glucose ([F-18]-FDG) and [F-18]-N-(3-fluoropropyl)-2-carbomethoxy-3-(4-iodophenyl)nortropane (F-18]-FP-CIT) microPET scans, as well as immunohistochemical (IHC) and immunofluorescent (IF) staining were conducted to evaluate the results. Results : The stepping test showed significant improvement of contralateral forelimb control in the HB-NSC group from 6-10 weeks compared to the control group (p<0.05). [F-18]-FP-CIT microPET at 10 weeks posttransplantation demonstrated a significant increase in uptake in the HB-NSC group compared to pretransplantation (p<0.05). In IHC and IF staining, tyrosine hydroxylase and human beta 2 microglobulin (a human cell marker) positive cells were visualized at the transplant site. Conclusion : These results suggest that the HB-NSC aggregates can survive in the striatum and exert therapeutic effects in a PD model by secreting dopamine.